DEVELOPMENT AND QUALITY ASSESSMENT OF FLAVORED PROBIOTIC ACIDOPHILUS MILK - M. Junaid; I. Javed; M. Abdullah; M. Gulzar; U. Younas; J. Nasir; N. Ahmad (Journal of Animal and Plant Sciences, 2013)
Functional foods containing probiotic bacteria (lactic acid bacteria and bifidobacteria) are getting popularity in the world, due to tremendous health benefits conferred by these bacteria. However, the total viable count of bacteria in the final product and the sensory attributes of the product are of higher importance for its consumer acceptability. In this study, flavored (strawberry, pineapple, and mango) probiotic acidophilus milk (from buffalo) using probiotic starter culture (Lactobacillus acidophilus) was prepared and its microbiological, physicochemical and sensory quality studies were carried out up to 6 days of storage. A slight increase in acidity of the milk was observed after 6 days of storage resulting in a decrease of pH (from pH 4.5 to 4.3). Total viable count of L. acidophilus bacteria was decreased after 6 days of storage due to increase in acidity but it was still within acceptable range (>106). Sensory evaluation data shows that the quality of sensory attributes (color, taste, aroma, appearance and overall acceptability) was slightly decreased after 6 days of storage but still had considerable acceptability.
Keywords: Functional foods; Probiotics; Lactobacillus Acidophilus; Acidophilus milk; Sensory evaluation; Keeping